MENGUNGKAP BATASAN KAIDAH DAMAIR DALAM QAWA’ID AL-TAFSIR KARYA AL-SABT: SEBUAH KRITIK KONSTRUKTIF - Hayatullah Hilmi Aziz; Ahmad Muhsin (LP2M Universitas Ibrahimy, 2024)
The book Qawa’id al-Tafsir by Al-Sabt is known for presenting the principles of Al-Qur'an interpretation in a systematic, economical, concise, and easily understandable manner. However, the book lacks explanations regarding the indications behind the unconventional use of Damair (pronouns), which causes anxiety among students. This study employs a descriptive-analytical method with a qualitative approach and falls under the category of library research. The results show that although Al-Sabt's book is well-structured, the lack of an in-depth explanation about the unconventional use of Damair leads to dissatisfaction and confusion among readers. It makes readers feel that the Al-Qur'an employs irregular principles without clear reasons. This deficiency underscores the importance of thorough explanations in using interpretative principles to enhance understanding and tranquillity for readers. This study highlights the urgency of explaining Damair's principles and offers a new perspective in the critical analysis of Al-Sabt's work. It contributes to the development of Al-Qur'an interpretation studies by providing insights into the importance of conveying the reasons behind using Damair principles in Al-Qur'an exegesis. These findings are expected to enrich the scholarly discourse on Al-Qur'an interpretation and serve as a reference for researchers and students.